Nanosecond colloidal quantum dot lasers for sensing - Laurand, N. (2014)
Low-threshold, gain switched colloidal quantum dot (CQD) distributed-feedback lasers operating in the nanosecond regime are reported and proposed for sensing applications for the first time to the authors’ knowledge. The lasers are based on a mechanically-flexible polymeric, second order grating structure overcoated with a thin-film of CQD/PMMA composite. The threshold fluence of the resulting lasers is as low as 0.5 mJ/cm2 for a 610 nm emission and the typical linewidth is below 0.3 nm. The emission wavelength of the lasers can be set at the design stage and laser operation between 605 nm and 616 nm, while using the exact same CQD gain material, is shown. In addition, the potential of such CQD lasers for refractive index sensing in solution is demonstrated by immersion in water.